Kontribusi Usaha Mikro Kecil, Dan Menengah (Umkm) Terhadap Kesejahteraan Masyarakat Besar Dalam Perspektif Ekonomi Islam - Atika, Atika (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2022)
MSMEs are self-sufficient economies that are completed by individuals or business elements that are not assistants or part of an organization that is claimed, controlled or part of, either directly or by implication from an organization that is claimed, controlled, controlled or part of either directly or indirectly. directly or by implication from mini, medium, or large organizations. At present the development of private companies is very rapid in the public sphere, in line with the encouragement of innovation and a large market interest in certain types of goods, for example palm oil which will be processed into value-added products. This type of check is a graphic check. While the various information procedures underline perceptions and opinion polls. In this audit strategy, the information used is information reduction, information presentation and decision making. Oil palm specialist MSME located in Sungai Badak City, Mesuji Region The Mesuji regime plays an important role for the community represented by the production of a new position with the presence of oil palm specialist MSME respondents facing a salary increase so they can fulfill their family needs such as food, welfare and protection moreover , instructive survival of their children.